2019
DOI: 10.1002/mgg3.990
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐182‐5p enhances in vitro neutrophil infiltration in Kawasaki disease

Abstract: BackgroundKawasaki disease (KD) patients could develop coronary artery lesion (CAL) which threatens children's life. A previous study identified KD biomarker miRNAs that could discriminate KD patients from febrile non‐KD patients. We wonder whether these KD prediction biomarkers could be further applied to predict CAL formation in KD patients.MethodsTo examine this hypothesis, we conducted a meta‐analysis, miRNA mimic transfection, in vitro cell model and microarray assays.ResultsWe first showed that miR‐182‐5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We further used the concentrations of the six protein biomarkers to derive KD prediction models with one type of machine learning algorithm, support vector machine (SVM, lib-svm version 3.22) to conduct the binary classification jobs as previous studies 21 , 28 . In summary, we first conducted tenfold cross validation to derive the best parameters, gamma = 0.03125 and cost = 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further used the concentrations of the six protein biomarkers to derive KD prediction models with one type of machine learning algorithm, support vector machine (SVM, lib-svm version 3.22) to conduct the binary classification jobs as previous studies 21 , 28 . In summary, we first conducted tenfold cross validation to derive the best parameters, gamma = 0.03125 and cost = 4.…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent ELISA validation identified KD biomarkers which enabled us to develop a high-performance KD prediction model. By using an in vitro cell model applied in a previous study 21 , we also investigated the pathogenic roles of S100A12 in KD. We concluded that S100A12 treatment promoted neutrophil cell infiltration through the endothelial layer in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, both neutrophil migration and transformation were associated with shock syndrome, a refractory response to IVIG and coronary artery lesions (CAL) in KD ( 34 36 ). Neutrophil activation has been reported to be enhanced with a marked increase in ROS, which contributes to the excessive formation of neutrophil extracellular traps (NETs), which has been suggested as being involved in the pathogenesis of KD ( 31 , 37 39 ), as well as the severity of acute respiratory syndrome caused by SARS-CoV-2 and severe COVID-19 patients who have cardiovascular injuries ( 40 42 ). One recent study profiled whole blood transcriptomes of COVID-19 patients and found that neutrophil activation signatures were predominantly enriched in the severe COVID-19 group, which was confirmed via granulocyte sample validation of an independent cohort of COVID-19 patients ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…found that the expression of miR-182-5p increased in the serum of patients with CALs compared to those without CALs. Through pathway enrichment and further experiments on human umbilical vein endothelial cells (HUVECs) and neutrophils, they concluded that miR-182-5p could enhance neutrophil infiltration to induce the CAL formation via activating the leukocyte trans-endothelial migration pathway ( 75 ). Besides, a recent pathway enrichment analysis revealed that the target genes of miR-223-3p are mainly distributed on the T cell receptor and B cell receptor pathways, which are highly relative to immune function ( 76 ).…”
Section: The Inherent Mechanism Of Mirnas In Kawasaki Diseasementioning
confidence: 99%